Exceedingly Fast Oxygen Atom Transfer to Olefins via a Catalytically Competent Nonheme Iron Species. (13th April 2016) - Serrano‐Plana, Joan; Aguinaco, Almudena; Belda, Raquel; García‐España, Enrique; Basallote, Manuel G.; Company, Anna; Costas, Miquel
Abstract: The reaction of [Fe(CF3 SO3 )2 (PyNMe3 )] with excess peracetic acid at −40 °C leads to the accumulation of a metastable compound that exists as a pair of electromeric species, [Fe III (OOAc)(PyNMe3 )] 2+ and [Fe V (O)(OAc)(PyNMe3 )] 2+, in fast equilibrium. Stopped‐flow UV/Vis analysis confirmed that oxygen atom transfer (OAT) from these electromeric species to olefinic substrates is exceedingly fast, forming epoxides with stereoretention. The impact of the electronic and steric properties of the substrate on the reaction rate could be elucidated, and the relative reactivities determined for the catalytic oxidations could be reproduced by kinetic studies. The observed fast reaction rates and high selectivities demonstrate that this metastable compound is a truly competent OAT intermediate of relevance for nonheme iron catalyzed epoxidations.